Polymorphisms and haplotypes in the Interleukin 17 Alfa gene: potential effect of smoking habits in the association with periodontitis and type 2 diabetes mellitus - Rimachi Hidalgo, Marco A. [UNESP]; Cirelli, Thamiris [UNESP]; da Silva, Bárbara Roque [UNESP]; Nicchio, Ingra Gagno [UNESP]; Nepomuceno, Rafael [UNESP]; Orrico, Silvana R. P. [UNESP]; Cirelli, Joni A. [UNESP]; Theodoro, Letícia Helena [UNESP]; Barros, Silvana P.; Scarel-Caminaga, Raquel M. [UNESP] (Springer Nature, 2021)
Few studies evaluate interrelationships between periodontitis (P) and Type 2 Diabetes Mellitus (T2DM). The aim of this study is to investigate the genetic susceptibility to periodontitis alone, or concomitant with T2DM (as comorbidities), analyzing single nucleotide polymorphisms (SNPs) in the Interleukin 17 alpha (IL17A) gene, considering the biochemical profile and smoking habits on the subjects’ periodontal status. We investigated 879 individuals divided into: T2DM subjects also affected by severe or moderate periodontitis (T2DM-P, n = 199); non-diabetics with severe or moderate periodontitis (PERIODONTITIS, n = 342); and healthy subjects (HEALTHY, n = 338). Subjects underwent complete periodontal examination, history of smoking habits, glycemic and lipid biochemical evaluation. DNA from buccal cells was utilized to genotype the SNPs rs2275913, rs3819024 and rs10484879. The impact of the subjects’ biochemical profile was analyzed in their periodontal status. Each SNP was analyzed independently, and as haplotypes, by multiple logistic regressions, adjusted for covariates, and also stratifying the groups by age, sex and smoking habits. Independently of the periodontitis degree, poorly-controlled T2DM subjects showed worse glycemic and lipid profile. Multiple logistic regressions demonstrated that smokers and former-smokers carrying the GG genotype of rs3819024 seemed to have higher risk for T2DM-Periodontitis (OR = 6.33; 95% CI = 1.26–31.77, p = 0.02), and mainly for T2DM alone (OR = 5.11; 95% CI = 1.37–19.06, p = 0.01), than never smokers. We found the potential effect of smoking habits in the association of IL17A-rs3819024-GG with diseased phenotypes. Because the observed wide confidence intervals, further studies enrolling larger populations, and SNPs’ functional evaluations are needed to better understand our findings.
Keywords: Diabetes Mellitus; Genetic Polymorphisms; Interleukin-17; Periodontitis